Writing and Risk: Magic, Occult, Exorcisms - Muir, Tom (Journal of Academic Writing, 2018)
What does it mean to take a risk when I write? Can I? Should I? The idea of risk has preoccupied a number of scholars recently, including those interested in discourse, writing and education (e.g. McWilliam 2009 and Thesen and Cooper 2014). This paper attempts to trace a concept of risk in academic writing, by asking questions about what “belongs” in academic texts and making use of bodies of knowledge that seem to be beyond the pale of academic discourse – magic, the occult, exorcisms. By thinking of risk as a side-effect of genres and traditions, I use the language of magic and the occult as a device to apprehend what academic reading cannot usually perceive, when there may be more in a text than academic reading can deal with. I draw examples from three inventive academic writers (Mary Scott, Yosef Hayim Yerushalmi and Nick Sousanis) to think about the benefits and consequences of risk in academic writing, and the limits of what Karen Bennett (2007) calls English Academic Discourse (EAD). I argue for a kind of writing that might, in the words of Jacques Derrida, anticipate the future ‘in the form of an absolute danger’ (1997: 5).